Pengaruh Penerapan Pendekatan Diferensiasi terhadap Kemampuan Pemecahan Masalah Matematis Siswa pada Materi Bentuk Aljabar - Azura, Fatma Mayzatul; Rakhmawati, Fibri (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to find out how the application approach influences students' ability to solve mathematical problems using algebra material. The differentiation approach used is process differentiation. This research uses a quantitative research approach with experimental methods in class VII Budisatrya Private Middle School. This research sample consisted of two groups, namely the experimental group VII-2, 25 students who used a differentiation approach, and the control group, Class VII-1, 25 students who used the conventional approach. This research design uses Pretest – Posttest Control Group Design. Research data was collected through mathematical problem solving ability tests both at the pre-test and post-test stages. The results of the analysis using the Independent Sample t Test with the IBM SPSS program showed results with one-sided and two-sided significance of p<0.001, which means that students who used the process differentiation approach were better at solving mathematical problems compared to students who used the conventional approach. In simple terms, the use of the process differentiation approach has a significant influence on students' ability to solve mathematical problems in algebraic material. Keywords: Differentiated Learning, Problem Solving Ability